Effects of karst environmental stresses on seed germination and seedling growth of alfalfa (Medicago sativa L.) - Zijun Zhou; Junqin Li; Yuting Yang; Yang Gao; Xiangtao Wang; Haiyan Huang; Rui Wang; Puchang Wang; Lili Zhao (Frontiers in Sustainable Food Systems)
Alfalfa (Medicago sativa L.) plays an important role in the development of animal husbandry in the karst region of southwestern China, and karst environmental stress has a significant impact on the germination of alfalfa seeds. This study subjected alfalfa seeds to calcium salt stress (0–100 mM), drought stress (0–0.53 MPa), and pH stress (pH 3–9). Germination indicators (germination rate, germination potential, germination index, and vigor index), seedling morphological indicators (shoot length and root length), and biomass indicators were measured to assess seed stress resistance. The results showed that mild drought stress (5% PEG solution) and weak alkaline stress (pH 8) promoted seed germination, and a 20 mM CaCl2 solution significantly increased the germination rate. The root system of seedlings was more sensitive to the three types of stress. Under moderate calcium stress (40 mM), only a slight decrease in tissue water content was observed. Under moderate drought stress (10% PEG), fresh weight and tissue water content decreased, but dry weight significantly increased. Under alkaline stress (pH 9), both biomass indicators and tissue water content increased. This study provides a theoretical reference for selecting plants suitable for cultivation in karst environments.